Tumor-associated M2 macrophages in the immune microenvironment influence the progression of renal clear cell carcinoma by regulating M2 macrophage-associated genes - Zhang, Xiaoxu; Sun, Yang; Ma, Yushuo; Gao, Chengwen; Zhang, Youzhi; Yang, Xiaokun; Zhao, Xia; Wang, Wei; Wang, Lisheng (Frontiers in Oncology, 2023)
Background: Renal clear cell carcinoma (RCC) has negative prognosis and high mortality due to its early diagnosis difficulty and early metastasis. Although previous studies have confirmed the negative progression of RCC is closely related to M2 macrophages in tumor-associated macrophages (TAMs) , the specific mechanism is still unknown Methods: We used immunofluorescence labeling and flow cytometry to detect the proportion of M2 macrophages in RCC tissues. And bioinformatics technique was used to obtain 9 M2 macrophage-related model genes, including SLC40A1, VSIG4, FUCA1, LIPA, BCAT1, CRYBB1, F13A, TMEM144, COLEC12. Using these genes, model formulas are constructed to devide samples into high and low risk groups, and then the overall survival (OS) , progression-free survival (PFS) and Gene set enrichment analysis (GSEA) of the high and low risk groups were analyzed. Real-time quantitative polymerase chain reaction (RT-qPCR) was used to measure the expression of model genes between normal kidney tissue and RCC tissue, as well as between HK-2 cell and 786-O cell. Besides, we induced the M2 differentiation of THP-1 cell, and then co-cultured with the RCC cell 786-O in transwell to observe what effect M2 macrophages will cause on the invasion, migration and the expression of model genes of RCC. Results: Our study demonstrated M2 macrophages in RCC was about 2 folds that of normal renal tissue (P<0.0001) and M2 macrophages affected the prognosis of patients with RCC by affecting the co-expressed genes, which were mainly enriched in immune-related pathways. The results of in vitro experiments showed that in RCC tissues and 786-O cells, the model gene FUCA1 was down-regulated, and SLC40A1, VSIG4, CRYBB1 and LIPA were up-regulated. Besides, the results of co-culture showed that after 786-O co-culture with M2 macrophages, the ability of migration and invasion was promoted and the expressions of FUCA1, SLC40A1, VSIG4, CRYBB1, LIPA and TMEM144 were all up-regulated. Conclusion: The proportion of tumor-associated M2 macrophages in RCC tissues is upregulated, and M2 macrophages promote the progression of RCC by regulating the expression of SLC40A1, VSIG4, FUCA1, LIPA, BCAT1, CRYBB1, F13A, TMEM144, COLEC12 genes, thereby affecting the prognosis of patients with RCC.